Non‐alcoholic fatty liver disease in a sample of individuals with bipolar disorders: results from the FACE‐BD cohort. (24th November 2020) - Godin, Ophelia; Leboyer, Marion; Belzeaux, Raoul; Bellivier, Frank; Loftus, Joséphine; Courtet, Philippe; Dubertret, Caroline; Gard, Sebastien; Henry, Chantal; Llorca, Pierre‐Michel; Schwan, Raymund; Passerieux, Christine; et al.
Abstract: Objective: Non‐Alcoholic fatty liver disease (NAFLD) is becoming the most common liver disease in Western populations. While obesity and metabolic abnormalities are highly frequent in bipolar disorders (BD), no studies have been performed to estimate the prevalence of NALFD in individuals with BD. The aim of our study is to estimate the prevalence of NAFLD and to identify the potential associated risk factors in a large sample of BD individuals. Methods: Between 2009 and 2019, 1969 BD individuals from the FACE‐BD cohort were included. Individuals with liver diseases, Hepatitis B or C, and current alcohol use disorders were excluded from the analyses. A blood sample was drawn from participants. Screening of NAFLD was determined using fatty liver index (FLI). Individuals with FLI> 60 were considered as having NAFLD. Results: The prevalence of NAFDL in this sample was estimated at 28.4%. NAFLD was observed in 40% of men and 21% of women. NAFLD was independently associated with older age, male gender, sleep disturbances, and current use of atypical antipsychotics or anxiolytics. As expected, the prevalence of NALFD was also higher in individuals with overweight and in those with metabolic syndrome. Conclusions: This study reinforces the view that individuals with BD are highly vulnerable to metabolic and cardiovascular diseases. The prevalence of NAFLD in individuals with BD was two times higher than the prevalence reported in the general population. The regular screening of the MetS in individuals with BD should be therefore complemented by the additional screening of NAFLD among these vulnerable individuals.